Molecular diagnosis usefulness for idiopathic anaphylaxis. Issue 3 (June 2020) - Cardona, Victoria; Guilarte, Mar; Labrador-Horrillo, Moises
Abstract : Purpose of review: Molecular diagnosis has become an indispensable tool in allergy. In suspected idiopathic anaphylaxis, it is mandatory to extend the diagnostic search to its limits. The current review evaluates how molecular diagnosis allows to identify a number of difficult to prove potential culprits. Recent findings: Depending on different geographical areas, it has been shown that the number of anaphylaxis labelled as idiopathic may decrease by the use of molecular diagnosis. The most relevant allergens identified are alpha-gal, omega-5-gliadin, Anisakis, lipid transfer proteins and oleosins. The role of cofactors has been shown to be relevant in a high proportion of cases. Mast cell disorders should always be ruled out. Summary: There is a need to provide further molecular diagnostic tests for use in clinical practice to identify sensitization to allergens not well represented in current commercial assays.